2021
DOI: 10.1007/s10212-021-00571-z
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of the reciprocal relationship between academic procrastination, study satisfaction, and dropout intentions in higher education

Abstract: Student dropout is a multi-causal process. Different theoretical models on student dropout consider dysfunctional study behavior (e.g., academic procrastination) and low study satisfaction as possible determinants of students’ dropout intentions during their university studies. However, these models neglect contemporary conceptualizations that assume reverse relationships between dropout intentions and other determinants of the dropout process. Until now, empirical evidence on these assumptions is scant. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 58 publications
3
41
0
2
Order By: Relevance
“…Furthermore, academic procrastination and loneliness appeared to consistently negatively relate to S-Content in both studies. The finding for academic procrastination is in line with Scheunemann et al (2021) who found a negative relationship between academic procrastination and 10. 3389/fpsyg.2022.918367 overall study satisfaction at each measurement point.…”
Section: Satisfaction With Study Contentsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, academic procrastination and loneliness appeared to consistently negatively relate to S-Content in both studies. The finding for academic procrastination is in line with Scheunemann et al (2021) who found a negative relationship between academic procrastination and 10. 3389/fpsyg.2022.918367 overall study satisfaction at each measurement point.…”
Section: Satisfaction With Study Contentsupporting
confidence: 90%
“…On a descriptive level, a few findings indicated a slight linear increase in overall study satisfaction over a period of 4 months ( Ng and Ye, 2016 ) and 6 months ( Allan et al, 2020 ) without considering the subdimensions. Contrary, Scheunemann et al (2021) found a decrease in overall study satisfaction over one semester. Currently, during the COVID-19 pandemic, decreases in study satisfaction are conceivable as students are exposed to several pandemic-related challenges ( Sahu, 2020 ).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…This type of psychoeducation can often have a normalizing effect, reducing shame and stigma, and, in turn, motivate behavior change. Similarly, career counselors might use the PDC in relation to discussing study satisfaction and dropout intentions in order to prevent students ending their studies prematurely ( Scheunemann et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Large panel studies such as the German National Educational Panel Study (NEPS; Blossfeld & Roßbach, 2019) or the German Socio-Economic Panel Study (SOEP; Goebel et al, 2019) often spanning several years of assessment are excellently suited to capture long-term changes in adaptation processes and to illuminate consequences of better or worse socioemotional adjustment for outcomes such as educational attainment. In these studies, participants are typically asked about global retrospective assessments of, for instance, their study satisfaction and drop-out intentions (e.g., Scheunemann et al, 2021), or the extent to which they feel they belong to their educational setting (e.g., Menkor et al, 2021).…”
Section: Background 11 Socioemotional Adaptationmentioning
confidence: 99%